(untitled) (Altre Modernità, 2011)
“Tuesday, September 11, 2001 dawned temperate and nearly cloudless in the eastern United States”. Thus begins Chapter One of the 9/11 Commission Report, a chapter that bears the title, “‘We have Some Planes’”. As with all good pop fiction, the reader awaits to see what this quote means, although we know already that it will mark a crucial moment, one that renders the innocuous urgent, or gives meaning to a startling chaos of coincidence. Pop culture has taught us the formula well: Everything looks fine; high school kids sip pop and dance in front of the juke box; Ole Doc Jones is mowin’ the lawn while Mrs. Jones makes lemonade. BUT strange noises have been heard in the cellar; no one can find the cat; Mr. Grundy insists he saw flashing lights last night, but no one believes him because Mrs. Grundy says he’s been acting strange ever since she flushed his Viagra; mysteriously, all the clocks in Indianapolis have started running fast or slow by exactly 24 hours. Then we hear the message on the police radio: “we’ve got some planes…as large as football fields hovering over every Wall-Mart in the nation”. At last someone will believe the geeky newspaper boy and his big brother’s girlfriend, who knew all along he was on to something. Let’s hope it’s not too late.